ChemInform Abstract: New Aspidofractinine, Aspidospermatan and Akuamiline Indole Alkaloids from the Roots of Kopsia singapurensis Ridl. Issue 17 (4th April 2013) - Ahmad, Kartini; Hirasawa, Yusuke; Nugroho, Alfarius Eko; Hadi, A. Hamid. A.; Morita, Hiroshi
Abstract Structures of three new aspidofractinines (I), (II), and (III), a new aspidospermatan (IV) and a new akuamiline (V) isolated from the roots of Kopsia singapurensis are elucidated.